PENGARUH TEKSTUR BUTIRAN PADA BEBERAPA KOMODITAS TERHADAP JUMLAH IMAGO HAMA Sitophylus oryzae L. (Coleoptera:Curculionidae) DI LABORATORIUM - Sri Wulandari; Syahrial Oemry; Yuswani Pangestiningsih (Universitas Sumatera Utara, 2014)
The effect of grain texture on several comodities to adult of Sitophilus oryzae L. (Coleoptera:Curculionidae) in laboratory” supervised by Syahrial Oemry and Yuswani Pengestiningsih. Thisreseach aims to know the effect of grain texture on several comodities to adult of S. oryzae. Thiswas done in Laboratory of Perum Bulog Kantor Divre SUMUT Medan since January untill March2013. The method of this research was Completely Randomized Design Non Factorial with eighttreatments and three replicants.The results showed that treatment of P5 , P7 , P1 , P3 at 165.33 ,163.33 , 150.00 , 78.67 tail, in the treatment greatly affect breeding S. oryzae . Whereas the finetexture of flour showed a decrease in population size in the treatment P2, P4, P6, and P8 at 8.33,8.33, 10.00, 10.00 tail . Texture on the surface of each type of feed greatly affects the proliferationof pests powder S. oryzae .Keywords:Texture of media, S. oryzae.